1984
DOI: 10.1007/bf01972339
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of histamine induced by intracerebral injection into mice

Abstract: Three methods were used to study the analgesic effect of intracerebral injection of histamine (Hi) on mice: the writhing test (acetic acid and phenylquinone), the electrical stimulation of the tail and the hot plate test. At doses higher than 2 micrograms, Hi inhibited the writhing syndrome significantly, and at doses of 10 micrograms or higher, Hi displayed a marked analgesic effect during both the electrical stimulation and hot plate methods. The saline injection produced only a negligible effect. Simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
5

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 22 publications
1
15
0
5
Order By: Relevance
“…Histamine, a pain-enhancing substance in the skin and spinal cord (Kajihara et al, 2010), reduces nociceptive transmission when injected directly into the brain (Glick and Crane, 1978;Chung et al, 1984;Bhattacharya and Parmar, 1985;Braga et al, 1992;Sibilia et al, 1992;Malmberg-Aiello et al, 1994;Thoburn et al, 1994). H 1 and H 2 receptors are thought to mediate this effect (Thoburn et al, 1994;Braga et al, 1996;Lamberti et al, 1996).…”
Section: Antinociceptive Profile For Brain Histaminementioning
confidence: 99%
“…Histamine, a pain-enhancing substance in the skin and spinal cord (Kajihara et al, 2010), reduces nociceptive transmission when injected directly into the brain (Glick and Crane, 1978;Chung et al, 1984;Bhattacharya and Parmar, 1985;Braga et al, 1992;Sibilia et al, 1992;Malmberg-Aiello et al, 1994;Thoburn et al, 1994). H 1 and H 2 receptors are thought to mediate this effect (Thoburn et al, 1994;Braga et al, 1996;Lamberti et al, 1996).…”
Section: Antinociceptive Profile For Brain Histaminementioning
confidence: 99%
“…Though still a matter of some controversy, its role as a putative central neurotransmitter is gaining acceptance. Centrally administered histamine has been recently reported to induce analgesia in mice [4]. These observations prompted us to investigate the effect of centrally administered histamine and histamine agonists on acute peripheral inflammation induced by carrageenin.…”
Section: Introductionmentioning
confidence: 99%
“…The cell bodies of this system are recognised only in the tuberomammillary nucleus (TMN) of the hypothalamus and their nerve fibres innervate all part of the CNS (Schwartz et al 1991). Several lines of evidence demonstrated that systemic or central injection of histamine or histamine agonists produces antinociception, suggesting the importance of the histaminergic system in pain regulation (Chung et al 1984). Peripheral histamine activates and sensitises itchspecific nociceptive C fibres (Schmelz et al 1997;Zendehdel et al 2012).…”
Section: Discussionmentioning
confidence: 99%